Kaposiform Hemangioendothelioma of the GI Tract: An Exception to Occam’s Principle in an Adult with SBO - Luis E. Aguirre; Robert A. Ali; Darcy A. Kerr; Mahsa Khanlari; Gilberto Lopes (Case Reports in Oncological Medicine)
Kaposiform hemangioendothelioma (KHE) is a rare and locally aggressive vascular tumor with histological features resembling Kaposi sarcoma and capillary hemangioma mainly occurring in children and adolescents. Approximately 200 cases have been reported since its original description in 1993, with the vast majority presenting at an early age as raised ill-defined lesions with a red-blue hue mainly involving the skin and soft tissues in the extremities. Cases in adults remain extremely rare. Herein, we describe the case of a 29 year-old man who presented with progressive abdominal pain for 4 months and signs of obstipation found to be consistent with small bowel volvulus. The patient underwent exploratory laparotomy and resection of 55 cm of necrotic small bowel followed by enteroenterostomy and anastomosis. Microscopic examination revealed KHE involving small intestinal mesentery, muscularis propria, and submucosa. His recovery was uneventful and he was discharged after stabilization, opting to manage him expectantly with abdominopelvic imaging and to monitor for development of Kasabach-Merritt phenomenon. To our knowledge, this represents the first reported case of this entity presenting as intestinal obstruction in an adult for which we also present a review of the existing literature and possible treatment options.